2009
DOI: 10.1016/s0140-6736(09)60740-6
|View full text |Cite
|
Sign up to set email alerts
|

Sequential docetaxel as adjuvant chemotherapy for early breast cancer (TACT): an open-label, phase III, randomised controlled trial

Abstract: SummaryBackgroundIncorporation of a taxane as adjuvant treatment for early breast cancer offers potential for further improvement of anthracycline-based treatment. The UK TACT study (CRUK01/001) investigated whether sequential docetaxel after anthracycline chemotherapy would improve patient outcome compared with standard chemotherapy of similar duration.MethodsIn this multicentre, open-label, phase III, randomised controlled trial, 4162 women (aged >18 years) with node-positive or high-risk node-negative opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
121
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(130 citation statements)
references
References 41 publications
7
121
0
2
Order By: Relevance
“…However, it is also important to consider the risk and toxicity of neoadjuvant chemotherapy for patients: a substantial proportion of patients (20%) experienced serious adverse events in the present study. The toxicity profile and incidence of grade 3 alopecia, nausea, neuropathy, febrile neutropenia, and asthenia is consistent with large prospective randomized trials in which patients are treated with anthracycline-and taxane-containing regimens [19,20]. This study is the first prospectively designed analysis of patients with ER-positive, HER2-negative tumors who received neoadjuvant chemotherapy that includes the assessment of the RS by Oncotype DX assay.…”
Section: Discussionsupporting
confidence: 74%
“…However, it is also important to consider the risk and toxicity of neoadjuvant chemotherapy for patients: a substantial proportion of patients (20%) experienced serious adverse events in the present study. The toxicity profile and incidence of grade 3 alopecia, nausea, neuropathy, febrile neutropenia, and asthenia is consistent with large prospective randomized trials in which patients are treated with anthracycline-and taxane-containing regimens [19,20]. This study is the first prospectively designed analysis of patients with ER-positive, HER2-negative tumors who received neoadjuvant chemotherapy that includes the assessment of the RS by Oncotype DX assay.…”
Section: Discussionsupporting
confidence: 74%
“…The disappointing intent-to-treat analyses of large, conventionally designed trials, such as TACT and tAnGo, suggests that further improvements in adjuvant treatment will require individualized therapeutic decisions [116,117]. Cell cycle phase analysis of breast and ovarian cancers has shown that it is tumours displaying the accelerated cell cycle phenotype that are most likely to show a clinically relevant response to S-or M-phase-directed agents (Table 1, Figure 3B) [3,74,110,111,118].…”
Section: Cell Cycle Phase Analysis As a Predictor Of Therapeutic Respmentioning
confidence: 99%
“…Later, anthracycline combinations were found to be slightly but significantly more effective than the CMF regimen [2]. More recently, several adjuvant phase III trials have shown that taxane regimens further reduce the likelihood of recurrence and death, compared to anthracycline-containing combinations [3][4][5][6][7][8][9][10], but the absolute benefit was again small, and some trials were unable to show any advantage for the taxane arm [11,12]. Taxanes and anthracyclines can induce some acute and chronic toxicities of considerable clinical concern.…”
Section: Introductionmentioning
confidence: 99%